The Psychology of Human Leadership How To Develop Charisma and Authority - Paschen, Michael; Dihsmaier, Erich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The book seamlessly links fundamental insights and practical approaches to address the most important leadership problems and challenges. Each of the 11 chapters takes a close look at a specific leadership aspect and explains how to develop personal leadership qualities, such as charisma, the ability to motivate others, assertiveness, and how to overcome crises and conflicts to create new structures. Ethical questions and possible negative developments in connection with leadership and power are also examined. Unlike conventional leadership manuals, this book on leadership goes beyond the standard 'recipes' and models by providing clear trains of thought as well as a psychological and philosophical basis, and by focusing on major achievements in terms of leadership, it creates a more profound understanding and holistic view of the subject of leadership, while promoting a genuine fascination for it.
1. The philosophy of leadership -- 2. Leadership, personality, and charisma -- 3. Leadership, psychology, and knowledge of human nature -- 4. Leadership, threats, and change -- 5. Leadership, challenge, and perspective -- 6. Leadership, culture, and custom -- 7. Leadership, the group and dynamics -- 8. Leadership, influence and communication -- 9. Leadership, power, dominance -- 10. Leadership, disorders, and problems of the powerful -- 11. Leadership, success, and morality.
Keywords: Economics; Industrial management; Applied psychology; Economics/Management Science; Business Strategy/Leadership.; Industrial, Organisational and Economic Psychology; Human Resource Management; Management/Business for Professionals